Revitalizing Community Participant: Overcoming Challenges in the Aftermath of an Oil Spill Disaster Preparedness in Kampung Tanah Merah Baru, Teluk Bintuni, West Papua - Siregar, Ronald; Koestoer, Raldi Hendro; Lestari, Fatma (Journal of Social Research, 2023)
This research aims to investigate the community profile and challenges faced by Tanah Merah Baru Village in Teluk Bintuni, West Papua, following diesel fuel spill disasters associated with transportation activities near an LNG exploration company operation. The study employs a comprehensive research methodology, combining quantitative surveys, qualitative interviews, and focus group discussions with community representatives and a company's oil spill response team. Data was collected and analyzed by using descriptive statistics and factor analysis through IBM SPSS Statistics Version 27 software. The findings reveal that the community profile is influenced by social, economic, and environmental factors. Additionally, there is a low level of awareness and community participation in handling diesel fuel spills and implementing the Oil Spill Contingency Plan (OSCP). Notably, variations exist in the perceptions and attitudes towards diesel fuel spills among community members who have previous exposure to the company’s operational environment. To enhance the community's profile and resilience, targeted efforts are required to provide information and training, thereby improving preparedness and response capabilities in handling diesel fuel spills effectively in Tanah Merah Baru Village, Teluk Bintuni, West Papua.